Predictors of falls and fractures leading to hospitalization in people with dementia - A representative cohort study - Sharma, S; Mueller, C; Stewart, R; Veronese, N; Vancampfort, D; Koyanagi, A; Lamb, S; Perera, G; Stubbs, B (Elsevier, 2018)
Background There is a paucity of representative data on risk factors for hospital admission due to falls and fractures in dementia. Thus, we investigated this using data from a large representative clinical cohort. Methods A historical cohort of people with diagnosed dementia between January 2007 and March 2013, aged >65 years, was assembled using data from the Maudsley BRC Case Register, from four boroughs in London serving a population of 1.3 million people. Falls and/or fractures leading to hospitalisation were ascertained from linked national records. Demographic data, cognitive test scores, medications, and symptom and functioning scores from Health of the Nation Outcome Scales (HoNOS65+) were modelled in multivariate survival analyses to identify predictors of falls and fractures. Results Of 8,036 people with dementia (63.9% female), 2,500 (31.1%, incidence rate 125.5 per 1,000 person-years) had a fall during the follow-up period and 1,437 (17.7%, incidence rate 65.5 per 1,000 person-years) had a fracture. In multivariable models significant predictors of falls were increased age, female gender, physical health problems, previous fall or fracture, vascular dementia versus Alzheimer’s disease, higher neighbourhood deprivation, non-cohabiting status, and problems with living conditions. Ethnic minority status was protective of falls (e.g. Caribbean/Asian ethnicity). Neither medications (including psychtropic), neuropsychiatric, cognitive or functional problems predicted hospitalized falls. Predictors of fractures were similar to those predicting falls. Conclusions Besides demographic and physical health-related factors, risk of hospitalization due to a fall or fractures is largely determined by environmental and socioeconomic factors, rather than neuropsychiatric symptoms, cognitive status, functioning or pharmacotherapy.